Perancangan Interior Daycare Center Sebagai 2nd Home Di Surabaya - Kwong, Juwita Priscella (Intra, 2015)
The busyness of career women who serve as housewives and also work for a living makes them lack the time to take care of their babies. Whereas the early education is the most important, when the kids are in "The Golden Age". For parents who are busy working, they will need a place like a second home for children that can care and attend to their stages of development. For the children, home has an important role in supporting the growth process. Daycare Center serves as a place where children could develop according to their needs and abilities. After studying literature and surveying daycare facilities in Surabaya, then established a facility that will be able to attend to the needs of children at age 6 months - 8 years with excellent standardization for the development of the children. Guiding and educating children by âplaying while learning and learning while playingâ method is the main foundation of this design plan.